Kinetics of Human Immunodeficiency Virus Type 1 Decay following Entry into Resting CD4(+) T Cells - Zhou, Yan (American Society for Microbiology, 2005)
In untreated human immunodeficiency virus type 1 (HIV-1) infection, most viral genomes in resting CD4(+) T cells are not integrated into host chromosomes. This unintegrated virus provides an inducible latent reservoir because cellular activation permits integration, virus gene expression, and virus production. It remains controversial whether HIV-1 is stable in this preintegration state. Here, we monitored the fate of HIV-1 in resting CD4(+) cells by using a green fluorescent protein (GFP) reporter virus carrying an X4 envelope. After virus entry into resting CD4(+) T cells, both rescuable virus gene expression, visualized with GFP, and rescuable virion production, assessed by p24 release, decayed with a half-life of 2 days. In these cells, reverse transcription goes to completion over 2 to 3 days, and 50% of the viruses that have entered undergo functional decay before reverse transcription is complete. We distinguished two distinct but closely related factors contributing to loss of rescuable virus. First, some host cells undergo virus-induced apoptosis upon viral entry, thereby reducing the amount of rescuable virus. Second, decay processes directly affecting the virus both before and after the completion of reverse transcription contribute to the loss of rescuable virus. The functional half-life of full-length, integration-competent reverse transcripts is only 1 day. We propose that rapid intracellular decay processes compete with early steps in viral replication in infected CD4(+) T cells. Decay processes dominate in resting CD4(+) T cells as a result of the slow kinetics of reverse transcription and blocks at subsequent steps. Therefore, the reservoir of unintegrated HIV-1 in recently infected resting CD4(+) T cells is highly labile.